ANALISIS SEMANTIK BAHASA TELEKS PT GARUDA INDONESIA KANTOR CABANG DENPASAR - I Ketut Sri Rahayuni; I Wayan Pastika; Made Sri satyawati (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
Telex language is a language uses many abbreviations in its making. It is certainly interesting to be searched as in communicating to avoid misunderstandings between the message giver and the message recipient. The purpose of this research is to find out the semantic analysis of telex language used in PT.Garuda Indonesia branch office Denpasar. Method used to analyze the data in this research was metode padan/equivalent (Sudaryanto, 1985:15). The main theory used to analyze this problem is Critical Discourse Analysis proposed by Van Dijk (1997).The findings show that semantic analysis of telex language in PT.Garuda Indonesia branch office Denpasar consists of background on telex language is stated that the telex writer received complaints from passengers; details on telex language are stated with a chronological sequence of events that cause problems both in terms of the documents and procedures that passengers should not be experienced; the purpose of telex language is stated with requests or orders from the writer to the relevant parties to clarify or follow up on existing problems so they will not experience the same problems in the future. The result of the second analysis is there are no presuppositions and nominalization elements occur in telex language in the data.